2019
DOI: 10.1002/gps.5156
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, rather than age of onset, is a better predictor for cognitive function in older adults with bipolar disorder

Abstract: Objectives The association between older‐age bipolar disorder and cognitive impairments may be mediated by vascular burden. The aim of the study was to examine the difference of cognitive function between older people with late‐onset bipolar disorder (LOBD) and early‐onset bipolar disorder (EOBD) by considering rigorous vascular risk burden evaluation, comprehensive cognitive tests, and relevant biochemistry data. Methods We recruited 95 outpatients aged over 55 with a DSM‐IV‐TR diagnosis of bipolar I disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, a previous study showed that plasma Hcy levels increased signi cantly with age in a Northeast Chinese population 10 . In addition, Chen PH et al 6 showed a signi cant association between higher plasma Hcy concentration and worse cognitive performance in patients with late-onset bipolar disorder. Taken together, age may play an important role in determining Hcy levels in both the healthy population and patients with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a previous study showed that plasma Hcy levels increased signi cantly with age in a Northeast Chinese population 10 . In addition, Chen PH et al 6 showed a signi cant association between higher plasma Hcy concentration and worse cognitive performance in patients with late-onset bipolar disorder. Taken together, age may play an important role in determining Hcy levels in both the healthy population and patients with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers, such as homocysteine (Hcy), kynurenic acid, C-reactive protein, and triiodothyronine, have been shown to be potential risk factors for schizophrenia [2][3][4][5] . Hcy interacts with NMDA receptors, induces apoptosis, triggers oxidative stress, injures mitochondrial function and leads to vascular damage, which played an essantial role in the occurrence and development of schizophrenia 6 . Elevated plasma Hcy levels might also contribute to cognitive de cits that are common in patients with schizophrenia, even when the analyses are corrected for the relevant covariates 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers, such as homocysteine (Hcy), kynurenic acid, C-reactive protein, and triiodothyronine, have been shown to be potential risk factors for schizophrenia 2 5 . Hcy interacts with NMDA receptors, induces apoptosis, triggers oxidative stress, injures mitochondrial function and leads to vascular damage, which played an essential role in the occurrence and development of schizophrenia 6 . Elevated plasma Hcy levels might also contribute to cognitive deficits that are common in patients with schizophrenia, even when the analyses are corrected for the relevant covariates 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they speculated that functional differentiation may play an important role in the development of HHcy in BD patients (Levine et al, ). A recent study found that Hcy was a better predictor for cognitive function in elderly BD patients (Chen et al, ), which may provide the support for Levine's point of view.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, they speculated that functional differentiation may play an important role in the development of HHcy in BD patients (Levine et al, 2005). A recent study found that Hcy was a better predictor for cognitive function in elderly BD patients (Chen et al, 2019), which may provide the support other studies have found that valproic acid use was significantly associated with elevated Hcy level only in children with epilepsy (Dinç & Schulte, 2018). The results of adult patients with epilepsy were contradictory (Dinç & Schulte, 2018).…”
Section: Discussionmentioning
confidence: 79%